Performa Pertumbuhan dan Kelangsungan Hidup Udang Vaname (Litopenaeus vannamei) dengan Padat Tebar 114 ekor/m² di Tefa Politeknik KP, Kupang - Kostakurta Bule, Alexander Boy; Lukmini, Aisyah; Rina, Timotius Ragga; Nuban, Sri Rahayu; Juanda, Shobikhuliatul J; Khairani, Nurul Fitri; Banggut, Emanuel D; Murtawan, Heri; Rahman, Ihsan Sanggar; Swari, Wahyu Dani (Universitas Batangahari Jambi, 2026)
This study analyzes the growth and survival performance of whiteleg shrimp (Litopenaeus vannamei) reared at a stocking density of 114 shrimp/m² during a 90-day period at the Teaching Factory of Poltek KP Kupang. Cultivation was conducted in a 350 m² pond using a combination of blind feeding and biomass-based feeding methods, with routine monitoring of water quality parameters including temperature, salinity, pH, dissolved oxygen, and water clarity. The average body weight (ABW) increased significantly from 2.59 g/shrimp at day 30 to 21.74 g/shrimp at day 90. The average daily gain (ADG) during the culture fluctuated between 0.13 and 0.42 g/shrimp/day, indicating good growth performance. Feed conversion ratio (FCR) was 1.18, indicating efficient feed utilization, while the survival rate (SR) reached 85.1%, reflecting effective management and favorable culture conditions. Water quality parameters remained within optimal national standards, supporting shrimp physiological processes. The findings suggest that whiteleg shrimp aquaculture at this stocking density yields good growth and high survival, offering practical insights to improve intensive vannamei shrimp farming, particularly in the Nusa Tenggara Timur region.